BiolCol: Technological Platform for the Dissemination of the Biological Reference Collection of Aquatic Macroinvertebrates - Caicedo-Chacón, Luz-Yamile; Barón-González, Henry-Javier; Sánchez-Pedroza, Juan-Carlos; Aguilar-Carreño, Carlos-Alberto; Vega-Otálora, Kevin-Santiago; Borja-Acosta, Kevin-Giancarlo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
UNISANGIL has one of Colombia's five collections of aquatic macroinvertebrates, being the only one in the Department of Santander. The bioinformatics platform "Biological Collection - BiolCol" seeks to digitize the biological reference collection of macroinvertebrates of UNISANGIL-CBMUS. The design of BioCol was led by three students and the coordinator of the GIBD-SI of the UNISANGIL Systems Engineering Program. The work methodology applied in the development process was Scrum. Additionally, we followed the method Sampieri proposed to identify the needs, establish the objectives, define the scope, formulate the projected activities over time, and define the deliverables for developing the application. Based on the Darwin Core standard used by the Colombian biodiversity information system (SiB Colombia), we designed the system architecture, built models, and designed the database. To develop the interface, we used Laravel for the back end and NodeJS for the front end, and we integrated the images and 3D models of those specimens with available information. The platform allows the online registration, storage, and visualization of information CBMUS collection specimens. It also generates a label with a QR code for each individual, which enables queries of the data stored for each specimen. Overall, this platform aims to facilitate the registration, administration, and dissemination of biological collection information for researchers and the community in general.